Recalibrating Pre-trial Detention in the EU: Key Findings and Recommendations from the RELEASE Project - Kusak, Martyna; Krężel, Kinga (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
This article presents the key findings of the EU-funded RELEASE project, which examined the use of pre-trial detention and its alternatives in five Member States: Bulgaria, Croatia, Greece, Poland, and Slovakia. It reviews the applicable European legal standards, analyses national practices, and highlights good practices identified over the course of the project. The article concludes with policy recommendations aimed at fostering a more consistent and rights-compliant use of pre-trial detention across the EU, through enhanced professional practice, targeted training, and awareness-raising.